Qualitative Loop Analysis of Social-Ecological Connectivity: The Case of Bima Bay, West Nusa Tenggara - Munawar Munawar; Luky Adrianto; Mennofatria Boer; Zulhamsyah Imran; Andi Zulfikar (Faculty of Fisheries and Marine Science, Brawijaya University, 2020)
The coastal area of Bima Bay will continuously experience increased development for the next few years along with its city development as “Waterfront City” and as a tourism village by the decision letter of the West Nusa Tenggara governor. The data used in this research are primary and secondary data with a purposive sampling method. The analysis results show that: 1) the basic network model does not significantly differ from the simulation model, 2) loop analysis based on seven scenario simulations combines six nodes with the assumption that if node Up, Ad, Hp, P, and Jv is unavailable, so the nodes gaining negative effect are Tt, Ti, Sp, II, Ic, and Dw. Sustainable management effort of the ecosystem in Bima Bay by observing the network connection between SES components to find out the component giving positive and negative effects in management policy-making. The simulation model using the goodness of fit test for model statistic obtains p-value 0.96 which means H0 received since p-value 0.96 > 0.05 points. There need sustainable efforts to maintain the Bima Bay ecosystem by observing the impact of network relation across the components in SES to find out the component with positive and negative impact in making management policies.